1998
DOI: 10.1159/000013397
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Transforming Growth Factor-Beta 1 Expression May Predict Peritoneal Fibrosis in CAPD Patients with Frequent Peritonitis Occurrence

Abstract: The efficiency of continuous ambulatory peritoneal dialysis depends on the permeability of the peritoneal membrane. Peritoneal fibrosis (PF) causes loss of the dialytic function. Several studies have indicated that PF is closely related to the proliferation of peritoneal fibroblasts and the deposition of extracellular matrix. Transforming growth factor-beta 1 (TGF-β1) plays a major role in stimulating extracellular matrix deposition. Frequent peritonitis occurrence may cause persistent TGF-β1 mRNA expression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 15 publications
0
53
1
Order By: Relevance
“…Margetts et al reported that active TGF-β1 induced a prolonged submesothelial fibrosis that might be in connection with elevated expression of α-smooth muscle actinpositive myofibroblasts in the interstitium (41,42). Increased dialysate concentrations of TGF-β1 were reported to correlate with poorer outcomes in PD patients, while they were thought to stimulate myofibroblastic response in mesothelial cells, which triggers peritoneal fibrosis (17,43). VEGF is also closely related to TGF-β1 activity during PD.…”
Section: Türk Nefroloji Diyaliz Ve Transplantasyon Dergisi Turkish Nementioning
confidence: 99%
See 1 more Smart Citation
“…Margetts et al reported that active TGF-β1 induced a prolonged submesothelial fibrosis that might be in connection with elevated expression of α-smooth muscle actinpositive myofibroblasts in the interstitium (41,42). Increased dialysate concentrations of TGF-β1 were reported to correlate with poorer outcomes in PD patients, while they were thought to stimulate myofibroblastic response in mesothelial cells, which triggers peritoneal fibrosis (17,43). VEGF is also closely related to TGF-β1 activity during PD.…”
Section: Türk Nefroloji Diyaliz Ve Transplantasyon Dergisi Turkish Nementioning
confidence: 99%
“…Evidence from clinical studies indicates TGF-β1 presence in the peritoneum, which is up-regulated during episodes of peritonitis. Elevated levels of TGF-β1 in dialysate concentrations have been shown to be associated with poorer outcomes in PD patients (8,9,17).…”
Section: Introductionmentioning
confidence: 99%
“…[6,7,12,13,[23][24][25] It is not clear yet which alleles cause higher amounts of the TGF-β1 protein.…”
Section: Codon 25mentioning
confidence: 99%
“…[5] TGF-β1-induced fibroblast proliferation, stimulation of collagen synthesis, and enhanced matrix accumulation contribute to the development of fibrogenesis. [6,7] TGF-βl gen polymorphisms in the signal sequence genetically may be responsible for increased TGFβl production. Seven polymorphisms in the TGF-βl gene have been reported in a great number of studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation